Impact of Agricultural Non-Point Source Pollution on River Water Quality: Evidence From China - Xu, Hanxiao; Tan, Xinxiang; Liang, Jie; Cui, Yuhu; Gao, Qiang (Frontiers in Ecology and Evolution, 2022)
Identifying the effect of agricultural non-point source pollutants on water quality plays an important role in finding the direction for water pollution management. To this end, this paper conducts an empirical study on the effect of the application amount of agricultural fertilizer on river water quality based on the panel data of 46 prefecture-level cities and 18 state-controlled water quality monitoring points through which the main streams of Yangtze River and Yellow River flow from 2004 to 2019, using NH3N as an indicator. It is found that: (1) The increase in agricultural fertilizer application amount will aggravate the deterioration of water quality, and the water quality pollution in the upper watershed will lead to transboundary pollution of the water quality in the lower watershed when also under the influence of precipitation. (2) The fertilizer application amount and fertilizer application intensity have a threshold effect on river water quality pollution. When the fertilizer application amount exceeds the threshold value of 11.496, and the fertilizer application intensity exceeds the threshold value of 7.991, the positive effect of fertilizer application on pollutants in rivers will be further enhanced. (3) Fertilizer application amount has a long-term effect on water quality through lagging effect, and as the number of lagging periods increases, the accumulative effect of the negative influence of fertilizer application amount will gradually rise. Based on the findings of the empirical study, it is proposed that the inter-basin and inter-regional synergy should be promoted in the prevention and control of agricultural non-point source pollution, and the overall top-level design of agricultural subsidies and agricultural environmental policies in the areas along the basin should be considered.